PENGARUH PEMBELAJARAN BERBASIS MULTIMEDIA DAN GAYA BELAJAR TERHADAP HASIL BELAJAR MENULIS BAHASA INDONESIA - Asep Muhyidin; Masrupi Masrupi (Jurnal Membaca Bahasa dan Sastra Indonesia, 2018)
This research aims to know: 1) the difference between the media of multimedia learning and conventional learning on learning outcomes writing Indonesian language; (2) differences in learning styles of students who have visual and auditory learning styles on learning outcomes writing Indonesian language ; (3) The effect of the interaction between the use of multimedia in teaching and learning styles on learning outcomes writing Indonesian language. The sample in this study amounted to 80 students consisting of 40 students in the experimental class and 40 students in the control class. The instrument used was the result of studying writing Indonesian language and learning style questionnaire. The method used is a quasi experiment with a 2x2 factorial design and test hypotheses with Anova two lanes. Research results obtained: 1) there is a difference between media multimedia learning and conventional learning on learning outcomes writing Indonesian language; It is derived from the value or significance probability of 0.000 <0.05 at significance level of 5%, which means that Ho rejected and H1 accepted; 2) there are differences in learning styles of students who have visual and auditory learning styles on learning outcomes writing Indonesian language; It is derived from the value or significance probability of 0.001 <0.05 at significance level of 5%, which means that Ho rejected and H1 accepted; and 3) there is interaction between the use of multimedia in teaching and learning styles on learning outcome writing Indonesian language; It is derived from the value or significance probability of 0.019 <0.05 at significance level of 5%, which means that Ho rejected and H1 accepted.